An overview of using fungal DNA for the diagnosis of invasive mycoses. (1st February 2022) - White, P. Lewis; Alanio, Alexandre; Brown, Lottie; Cruciani, Mario; Hagen, Ferry; Gorton, Rebecca; Lackner, Michaela; Millon, Laurence; Morton, C. Oliver; Rautemaa-Richardson, Riina; Barnes, Rosemary A.; Donnelly, J Peter; et al.
ABSTRACT: Introduction: Fungal PCR has undergone considerable standardization and, together with the availability of commercial assays, external quality assessment schemes, and extensive performance validation data, is ready for widespread use for the screening and diagnosis of invasive fungal disease (IFD). Areas Covered: Drawing on the experience and knowledge of the leads of the various working parties of the Fungal PCR initiative, this review will address general considerations concerning the use of molecular tests for the diagnosis of IFD, before focusing specifically on the technical and clinical aspects of molecular testing for the main causes of IFD and recent technological developments. Expert Opinion: For infections caused by Aspergillus, Candida, and Pneumocystis jirovecii, PCR testing is recommended, and combination with serological testing will likely enhance the diagnosis. For other IFD (e.g. mucormycosis), molecular diagnostics represent the only non-classical mycological approach toward diagnoses, and continued performance validation and standardization have improved confidence in such testing. The emergence of antifungal resistance can be diagnosed, in part, through molecular testing. Next-generation sequencing has the potential to significantly improve our understanding of fungal phylogeny, epidemiology, pathogenesis, mycobiome/microbiome, and interactions with the host, while identifying novel and existing mechanisms of antifungal resistance and novel diagnostic/therapeutic targets.